A methodology of improvement of manufacturing productivity through increasing operational efficiency of the production process - Trojanowska, Justyna (2018)
One of the most important aspects of manufacturing efficiency assessment is the determination of productivity. A study of the relevant literature and a review of business practices have led the authors to conclude that there is a niche for a comprehensive decision support methodology which would assist organizations in improving their manufacturing productivity. This paper presents a methodology of improvement of manufacturing productivity through increasing operational efficiency of the manufacturing process. The methodology was verified by a manufacturing company which is a supplier of goods for i.e. the automotive and medical industries. The effect of using methodology is reducing of cycle of lot, reducing number of changeovers and eliminating errors.